Biological mediated synthesis of reduced graphene oxide (rGO) as a potential electron shuttle for facilitated biological denitrification: Insight into the electron transfer process. Issue 5 (October 2022) - Li, Jie; Li, Yi; Chen, Pengli; Sathishkumar, Kuppusamy; Lu, Yumiao; Naraginti, Saraschandra; Wu, Yunbo; Wu, Haisuo
Abstract: Ecofriendly electron shuttle for facilitated biological nitrate removal is essential for the sustainable development goals. The facilitated biological nitrate removal was investigated using ecofriendly green synthesized reduced graphene oxide (rGO) utilized as electron shuttle. The prepared rGO was characterized by XRD, SEM, XPS and used as electron shuttle for the facilitated biological nitrate removal by batch experiments under visible light irradiation condition. The addition of rGO significantly enhances the nitrate removal by donating the electrons, maximum nitrate reduction from 100 mg/L to 9.3 mg/L was observed within 72 h. GO-biodenitrification, rGO-biodenitrification system had electron transport system activity values of 0.79 and 0.89 µg O2 µg −1 min −1, respectively. rGO-biofilm shows significantly increased photocurrent response high photocurrent response was ascribed to increased charge separation and their active electron transfer to electroactive bacteria to facilitate the denitrification. Decreased electrostatic repulsion between photocatalyst and nitrate ions may facilitate the separation of nitrate to the photocatalyst surface and facilitate the nitrate reduction, also photoelectrons were transferred to the electroactive bacteria which can utilize the electrons and facilitate the nitrate reduction process. The most dominant genus Pelolinea, Ignavibacterium, Nitrospira, Paracoccus, Sorangium, Tepidiforma, Gemmatimonas, Chloroflexus, Treponema and Bdellovibrio was determined and actively involved in the denitrification process. Overall, the present study suggested that green synthesized rGO can be used as eco-friendly electron shuttle for the facilitated biological denitrification. Graphical Abstract: ga1 Highlights: Eco-friendly bio mediated reduced graphene oxide (rGO) were prepared. Facilitated biological denitrification was investigated using rGO. Photocurrent and Electron transport system activity was increased by rGO. Pelolinea, Ignavibacterium, Nitrospira were actively involved in denitrification.